Maternal Factors Influencing Low Birth Weight in West Pokot County, Kenya - Chelobei, Leah; Kimeto, Pamela; Bor, Wesley (KABARAK UNIVERSITY, 2019)
Worldwide an estimated 20% babies are born LBW and the impact of LBW on infant mortality is enormous. Child survival and development need more focus on healthy start of life. The objective of this study was to investigate maternal characteristics associated with LBW. Cross-sectional mixed study design was employed to collect data from7randomly selected health facilitiesusing interviewer administered questionnaire. A sample of 223 eligible mothers was selected and associations analyzed using chi square tests and regression analysis to confirm their statistical significance. Maternal nutrition; MUAC (B = 1.890, p=0.045), Antenatal Care attendance (B=2.236 p<0.001), Mothers education (B = 1.399, p=0.003), marital status (B=-5.647, p<0.001), FGM (B = 1.532, p<0.001). Sociodemographic and cultural characteristics were strongly predictivein mothers giving birth LBW babies. Interventions that focus on improving the socio- demographic characteristics recommended improving birth outcome (LBW).
FULL TEXT
Keywords: Maternal, Influence, Low Birth Weight, West Pokot